Diagnóstico do estado de conservação e das áreas de ocorrência dos recursos genéticos de abóboras (Cucurbita spp.), na agricultura familiar do Maranhão - Rodrigues, Raimundo Calixto Martins (2008)
The traditional agriculture is practice in parts different of the country, is traditional in Maranhão, where stands out the cultivation of several Cucurbitacea species (Citrullus spp., Cucurbita spp., Cucumis spp. and, in small scale, Lagenaria siceraria and Luffa cilyndrica), that although not being original of Brazil presents great genetic variability. Among the existent species, to those of the Cucurbit gender were introduced by the Indians and they are maintained in the traditional agriculture with an own evolutionary dynamics for each species, where the farmers use the own seed for the planting. Part this variability it was rescued and it is preserved in Active Banks of Germoplasm (ABGs). However, the local populations of pumpkin of Maranhão are being threatened of loss by several reasons, as rural exodus, activity change, once the pumpkin cultivation doesn't receive incentives of prices compensators, strong competition with other cultures of great expression as the soy, planting of forest essences as the Eucalyptus among others. Like this, that research had as objective diagnoses the areas of production of pumpkins in the State of Maranhão, identifying areas with cultivation of local populations and risks of genetic erosion. They were accomplished four expeditions that involved eleven municipal districts where were applied questionnaires into producers. It was verified that the municipal district of Buriticupu and the area of the small town from Maranhão were the main places of origins of the pumpkins with commercial value and that significant cultivations of local population existent. It was also verified that C. moschata is more thoroughly cultivated. It was identified a risk of genetic erosion related, mainly, the substitution of the cultivation for commercial varieties or others cultures.